2022
DOI: 10.3390/biotech11030025
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Door with CRISPR: Genome Editing of CCR5 and CXCR4 as a Potential Curative Solution for HIV

Abstract: Human immunodeficiency virus (HIV) infection can be controlled by anti-retroviral therapy. Suppressing viral replication relies on life-long medication, but anti-retroviral therapy is not without risks to the patient. Therefore, it is important that permanent cures for HIV infection are developed. Three patients have been described to be completely cured from HIV infection in recent years. In all cases, patients received a hematopoietic stem cell (HSC) transplantation due to a hematological malignancy. The HSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 105 publications
0
10
0
Order By: Relevance
“…CCR5 is the major gene target for the handful of R5-tropic HIV cures in humans ( 32 ). We and others reported that HIV Elite controllers and Viremic controllers (ECs/VCs) had lower CCR5 expression levels ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…CCR5 is the major gene target for the handful of R5-tropic HIV cures in humans ( 32 ). We and others reported that HIV Elite controllers and Viremic controllers (ECs/VCs) had lower CCR5 expression levels ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the treatments options remain limited for some patients with multiclass resistance and must be taken for life as they do not target the integrated proviral genome and fail to eradicate the virus in so called viral reservoirs. From this point of view, recent advances in genome editing offer encouraging prospects not only for blocking viral entry by modifying CCR5, but also for excising HIV sequences integrated into the genome [ 204 ]. One can hope that the combination of all these new therapeutic approaches will bring us closer to the development of an effective antiviral treatment against HIV that will be affordable for the broadest possible populations.…”
Section: Discussionmentioning
confidence: 99%
“…CCR5 gene editing —Recent advances in genome editing offers unprecedented possibilities for gene therapy, as it is now possible to replace one or more bases in any gene of interest, at any location [ 203 , 204 ]. The CRISPR/Cas9 system or the use of zinc finger nucleases (ZFN) are methods of choice for such gene editing [ 205 , 206 ].…”
Section: Targeting Ccr5 To Fight the Virusmentioning
confidence: 99%
“…The authors suggest that transplantation of CRISPR gene edited allogeneic hematopoietic stem cells may be a safe and an effective tool for HIV resistance. The most effective, long-term solution would be a successful bone marrow transplantation with CRISPR/Cas9 CCR5 edited hematopoietic stem cells [27,28]. However, further exploration and precision of CRISPR/Cas9 technology is needed prior to clinical trials (Figure 3).…”
Section: Genetic Engineering Of Hematopoietic Stem Cellsmentioning
confidence: 99%